Hepatocyte Mitogen‐Activated Protein Kinase Kinase 7 Contributes to Restoration of the Liver Parenchyma Following Injury in Mice. Issue 6 (28th May 2021) - Ooshio, Takako; Yamamoto, Masahiro; Fujii, Kiyonaga; Xin, Bing; Watanabe, Kenji; Goto, Masanori; Okada, Yoko; Suzuki, Akira; Penninger, Josef M.; Nishina, Hiroshi; Nishikawa, Yuji
Abstract : Background and Aims: Mitogen‐activated protein kinase kinase (MKK) 7 and MKK4 are upstream activators of c‐Jun NH2 ‐terminal kinases (JNKs) and have been shown to be required for the early development of the liver. Although it has been suggested that MKK7 might be involved in the regulation of hepatocyte proliferation, the functional role of MKK7 in the liver has remained unclear. Approach and Results: Here, we examined phenotypic alterations in liver‐specific or hepatocyte/hematopoietic cell–specific MKK7 knockout (KO) mice, which were generated by crossing MKK7 LoxP/LoxP with albumin–cyclization recombination (Alb‐Cre) or myxovirus resistance protein 1–Cre mice, respectively. The livers of Alb‐Cre −/+ MKK7 LoxP/LoxP mice developed without discernible tissue disorganization. MKK7 KO mice responded normally to liver injuries incurred by partial hepatectomy or injection of CCl4 . However, tissue repair following CCl4 ‐induced injury was delayed in MKK7 KO mice compared with that of control mice. Furthermore, after repeated injections of CCl4 for 8 weeks, the liver in MKK7 KO mice showed intense fibrosis with increased protractive hepatocyte proliferation, suggesting that MKK7 deficiency might affect regenerative responses of hepatocytes in the altered tissue microenvironment. MKK7 KO hepatocytes demonstrated normal proliferative activity when cultured in monolayers. However, MKK7 KO significantly suppressed branching morphogenesis of hepatocyte aggregates within a collagen gel matrix. Microarray analyses revealed that suppression of branching morphogenesis in MKK7 KO hepatocytes was associated with a reduction in mRNA expression of transgelin, glioma pathogenesis related 2, and plasminogen activator urokinase‐type ( Plau ); and forced expression of these genes in MKK7 KO hepatocytes partially recovered the attenuated morphogenesis. Furthermore, hepatocyte‐specific overexpression of Plau rescued the impaired tissue repair of MKK7 KO mice following CCl4 ‐induced injury. Conclusions: MKK7 is dispensable for the regenerative proliferation of hepatocytes but plays important roles in repair processes following parenchymal destruction, possibly through modulation of hepatocyte–extracellular matrix interactions.